A Guide to Evaluation of Value for Money in UK Public Services - and King, Julian; Hurrell, Alex (Verian, 2024)
When assessing value for money (VfM), there are sound arguments for combining insights from economics and evaluation. Drawing on the complementary strengths of both disciplines supports comprehensive assessment of policies and programmes’ VfM. In this Guide we introduce an interdisciplinary approach, Value for Investment, that integrates methods and tools from both disciplines, and which has gained traction worldwide. Among the concepts and methods of evaluation that economics brings to this interdisciplinary mix is cost-benefit analysis (CBA), which evaluates whether an intervention creates more value for society than it consumes. CBA is vital in the UK policy context, acting as a key tool for evaluating public policies, programmes, and projects as set out in the Green Book, HM Government’s central guide for appraisal and evaluation, and the Magenta Book which focuses on evaluation methodologies and practices across the whole policy cycle. Together, the Green Book and Magenta Book form a robust framework for evidence-based policymaking, ensuring CBA informs sound decision-making and evaluates implemented policies’ impacts. Within this policy context, value for money (VfM) is often framed as an objective or question within an evaluation and is commonly equated with CBA. However, we argue that while CBA contributes important evidence, it may be insufficient. The approach set out in this Guide includes economic analysis while integrating multiple values (social, economic, environmental, and cultural) and diverse evidence sources (quantitative and qualitative) for a more comprehensive VfM assessment, drawing on the strengths of CBA without limiting the evaluation to economic methods and metrics alone. The Value for Investment approach uses mixed methods (integrating quantitative and qualitative evidence), employs evaluative reasoning (interpreting evidence through the lens of explicit criteria and standards – improving transparency in the rationale for evaluative judgements), and is participatory (involving stakeholders in co-design and analysis). It is designed to be intuitive and practical to use by following a logical sequence of steps. The Value for Investment approach was developed through doctoral research (King, 2017; 2019) and refined through real-world VfM evaluations in diverse contexts. Leading examples of its application are published in Assessing Value for Money – the Oxford Policy Management Approach (King, Wate, Namukasa, Hurrell, Hansford, Ward, & Faramarzifar, 2023), and Value for Investment – Application and Insights (King, Crocket, & Field, 2023). This Guide is designed to complement existing VfI guidance by focusing on the interface between CBA and other evaluation methods to provide sound answers to VfM questions in the context of UK public policy.